The influence of intangible assets disclosures on businesses’ performance - Samara, Husni; Aladwan, Mohammad; Hamdan, Montaser; Atta, Anas Ahmad Bani (Asian Development Policy Review, 2023)
The purpose of this research is to determine how intangible asset declarations affected manufacturing companies listed on the Palestine Exchange in terms of performance throughout the years [2017-2021]. The study sample consisted of 13 industrial companies listed on the Palestinian Stock Exchange, and in order to verify the study hypotheses, a descriptive analytical approach was followed. Several statistical methods were used, such as random effect analysis. After conducting the required tests, the results of the tests showed that the intangible assets do not have an effective impact on the performance of the companies that were studied, as the relationship was negative and it was not proven that the intangibility of assets had any positive results. However, it was found that leverage has a positive effect on the performance of these companies. The study recommended that the approaches for service and industrial companies should be improved and developed to enhance the level of performance in accordance with developments that occurred in the financial market.